Choice of LIbrarianship as Career: A Case Study of EUYE Pioneer Library and Information Science Sstudents - Isaac Oluwadare Busavo (IJoLIS, 2024)
Purpose: This study determine the facotrs thAT shape studnets selectionof Library and InformATion Sciences (LIS) AS DISCIPLINE/Career at the Fedeal Univesity OYe-Ekin (EUYE) in Nigeria.